ANALISIS IMPLEMENTASI IZIN KERJA DI KETINGGIAN TERHADAP KECELAKAAN KERJA DI PT. X - Helmi Tri Wahyuadi; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Work permit is a written document that is used as a condition in carrying out hazardous work with due regard to the potential hazards that exist and anticipated action, also how to control it. Jobs that have the potential hazards are working at height. In PT. X ever happened of occupational accidents related to work at height up to cause the loss of working hours and even days of work. In the application of work permits, PT. X is still less than the maximum, and not in accordance with SOP (Standard Operating Procedure), in the approval of work permits. The purpose of this study was to analyze aspects of the implementation of the work permit in height, at an occupational accidents in PT. X. This research is a qualitative descriptive research method conducted in-depth interviews and field observations. This research subject is the main informant five workers at height, while the informant triangulation from HSE and foreman. Based on the results of the research, knowledge of workers about work permit has been good, with their ability to carry out the implementation of a work permit is good enough, the workers are also in accordance with the requirements of the company, most of the implementation of the work permit at height of at PT. X is not in accordance with the applicable Standard Operating Procedures, control assessments by the hierarchy of controls as substitution, administration, and using personal protective equipment. It is necessary to add the material of the work permit at height on the time of socialization, improving distribution, documentation, management and evaluation system of work permits and coordinated cooperation in the occupational health and safety division.